Do Institutional and Banking Cost Affect Investment in ASEAN? - Asfi Manzilati; Silvi Asna Prestianawati; Tsumma Lazuardini Imamia (AIBPM Publisher, 2022)
ASEAN is one of the actors in the world economy. With the launch of Forging Ahead Together, it is hoped that ASEAN can strengthen its economy and attract foreign investors to invest. The entry of large foreign investment into ASEAN is an opportunity for global investors. On the other hand, the factors that affect investment are from economic as well as non-economic. One important economic factor is banking costs because investment activities are inseparable from the presence of the financial sector which can cause costs and prices. Meanwhile, non-economic factors include institutional costs arising from the quality of a country's governance. This study uses a quantitative approach with panel regression analysis method to determine whether economic factors, namely bank costs or non-economic factors, affect the level of investment in ASEAN countries.